2013
DOI: 10.2519/jospt.2013.4441
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric Testing Supports the Use of 5 Questionnaires Adapted Into Brazilian Portuguese for Patients With Shoulder Disorders

Abstract: isorders of the shoulder region cause pain and limitation in movement and can affect functional abilities, professional and sports activities, as well as activities of daily living, and can ultimately affect quality of life.7 Studies conducted in Europe and North America estimated that roughly half of the population has at least 1 episode of shoulder pain a year, which results in high cost of treatment. 7,39,47 Current practice standards suggest that standard clinical measurements of muscle strength and joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
1
24
1
3
Order By: Relevance
“…2 Likewise, our MDC 90 for the QuickDASH was 12.85 points, compared to values ranging from 11 to 15.7 points in the literature, 1,14,23,27,30,31 whereas the MDC 95 reported on the DASH website ranges from 16 to 20 points. 20 It is important to recognize that (a) the MDC values reflect the specific ICC and standard deviation values in each particular study, and therefore different groups of patients would be expected to generate different values; (b) changes below the MDC threshold could be interpreted at an individual level as random fluctuations in score rather than actual change 39 ; and (c) the lower the reliability coefficient, the greater the SEM and the higher the MDC will be.…”
Section: Discussionmentioning
confidence: 82%
“…2 Likewise, our MDC 90 for the QuickDASH was 12.85 points, compared to values ranging from 11 to 15.7 points in the literature, 1,14,23,27,30,31 whereas the MDC 95 reported on the DASH website ranges from 16 to 20 points. 20 It is important to recognize that (a) the MDC values reflect the specific ICC and standard deviation values in each particular study, and therefore different groups of patients would be expected to generate different values; (b) changes below the MDC threshold could be interpreted at an individual level as random fluctuations in score rather than actual change 39 ; and (c) the lower the reliability coefficient, the greater the SEM and the higher the MDC will be.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, a study in patients with shoulder complaints, including specific pathology and postoperative shoulder patients, concluded that the PSFS was a reproducible, valid, and responsive instrument for measuring disability. 42 In general, the PSFS scored positively on agreement, test-retest reliability, construct validity, and responsiveness. 2,26 Overall, PSFS scales were more responsive than various musculoskeletal condition-specific questionnaires.…”
Section: T T Methodsmentioning
confidence: 99%
“…The test-retest reliability, construct validity, and responsiveness of the NPRS for measuring shoulder pain have been supported in various studies. 34,42 We instructed patients to choose the number that corresponded best with their current pain intensity level and their worst and least amount of pain in the last 24 hours. To best determine the amount of pain over the last 24 hours, the average of these 3 measures was used.…”
Section: Measurementsmentioning
confidence: 99%
“…A queixa de dor no ombro foi considerada quando a pontuação no questionário Shoulder Pain and Disability Index (SPADI) 17 foi igual ou maior a 30 pontos. Considerando que o SPADI não apresenta uma classificação da pontuação em níveis de severidade da disfunção, este ponto de corte foi estabelecido com base no estudo de Puga et al 18 …”
Section: Amostra Do Estudounclassified
“…O questionário SPADI representa uma das ferramentas mais recomendadas para avaliação das disfunções de ombro e a versão brasileira é confiável, válida e responsiva 17,18 . O questionário apresenta um domínio de dor com cinco itens e outro domínio de incapacidade, com oito itens, pontuados em uma escala de avaliação numérica de 10 pontos, de modo que zero indica sem dificuldade ou sem dor e dez indica não conseguiu fazer ou pior dor.…”
Section: Procedimentosunclassified